BUDIDAYA TANAMAN SEHAT KOMODITAS UNGGULAN DI SEMBALUN BUMBUNG - Sunantara , Aditya Aji; Utami, Nila Fitria; Husna, Risqiatul; Janiarti, Janiarti; Devi, Ni Made Sathya Paramitha; Attilla, Lalu Faiz Muhammad; Wardani, Novita Susila; Arista, Nada; Rizalandri, Ahmad; Sarjan, Muhammad (Jurnal Wicara, 2024)
The growing concerns from consumers about the safety of conventional food products, which are produced through the use of chemical fertilizers and synthetic pesticides in agriculture, are discussed. The uncontrolled use of chemicals is leading to environmental pollution, such as soil and water contamination, and increasing chemical residues in food products. Additionally, pests and plant diseases are becoming more resistant to pesticides, forcing farmers to use more chemicals, which further increases the accumulation of harmful residues in food. This issue arises because many farmers do not yet understand proper agricultural practices, as outlined in Good Agricultural Practices (GAP). GAP is a certification system implemented to ensure that agricultural production processes use advanced, environmentally friendly, and sustainable technologies, ensuring that the products are safe for consumption, worker welfare is guaranteed, and farming provides economic benefits. However, the implementation of GAP in the field remains low due to high costs, complex procedures, and the limited socio-economic conditions of farmers. GAP is also crucial for restoring agricultural land that has been degraded by chemical use. The development of GAP for sustainable agriculture can be achieved through a SWOT strategy, which involves increasing training and demonstrations for farmers, submitting requests to the Food Security Agency (BKP) to improve extension facilities, enhancing knowledge and skills related to GAP, and increasing interaction with universities and research institutions.